Multisensory Approach in Memorizing the Al-Quran for Early Childhood: Integration of the Tradition of Memorizing the Al-Quran with Digital Technology - Achmad Faqihuddin; Mokh Iman Firmansyah; Abdillah Muflih (AL-ISHLAH: Jurnal Pendidikan, 2024)
Introducing the Quran to early childhood is a crucial foundation for developing their character and spirituality. In the modern technological era, adopting an effective learning approach is essential. This article reviews the significance of a multisensory approach in Quran memorization for early childhood. This study employed a mixed-methods approach, involving a survey of 50 parents selected through convenience sampling who participated in the tahfidz program. In addition, in-depth interviews were conducted with seven parents and three early childhood tahfidz teachers, complemented by direct observation of interactions in the memorization process. Data analysis was performed descriptively using MS Excel 2013 for quantitative data and NVivo 12 for qualitative data, based on the Miles and Huberman approach. The results indicate that the tradition of Quran memorization remains strong in Muslim families and is increasingly applied to early childhood. Methods involving multiple senses—such as hearing, sight, and touch—are preferred to enhance memorization. The integration of technology, combining audio, visual, and kinesthetic elements, creates an engaging memorization experience. This study confirms that a multisensory approach, along with technology integration and the active involvement of parents and teachers, enhances children's engagement and memory retention. It also provides a robust foundation for developing an effective religious education curriculum.